Courage in the Government of Passions: Notes on Plato and the Ancient Cynics - Hoyos Sánchez, Inmaculada (ΠΗΓΗ/FONS, 2020)
The following paper compares Plato’s proposal with the approach of cynicism concerning the virtue of courage. The first section studies role of musical education in the Republic, which contributes to foster real courage among the guardians and avoids brutality. The second section exposes the differences between Platonism and Cynicism. The latter presented a new way of understanding courage, as a way of life, which does not require a musical pedagogy, but training in overcoming shame. Courage, according to the Cynics, is not the specific virtue of a class but is a way of life that any individual can adopt.